Development of RFID EPC Gen2 Tag for Multi Access Control System - Evizal Evizal; Tharek Abd. Rahman; Sharul Kamal Abdul Rahim; Sri Listia Rosa (Institute of Advanced Engineering and Science, 2013)
A Radio Frequency Identification (RFID) use radio waves to identify an object, this technology become useful for the future because of the advantages. Access system using RFID card is commonly used in a building, parking area, housing complex, etc. This paper explore and develop the use of RFID EPC Class1 Gen2 tag for multipurpose access system for identification and access control, such as personal identity identification, door access control and gate entry permit or access control. With the same tag Identity (ID) user can access many areas. RFID EPC Class1 Gen2 tag working at UHF band 902-928 MHz, this type of tag more suitable for multi access control because of scaterring technique in reading for the tag, as for gate access need longer distance read range. All users ID and information stored at the one central database, every transaction at the controlled were recorded in a control system.DOI:http://dx.doi.org/10.11591/ijece.v3i6.3855